667.287.5 Kimyo va kimyoviy texnologiyalar: INVESTIGATION OF PHTHALOCYANINE DIAMIDOPHOSPHATE- COPPER BY THERMAL ANALYSIS - Yusupov, Muzafar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article presents the results of a study of the synthesis of a new type of pigment - copper phthalocyanine diphosphate (DAPCuPc), which contains macroheterocyclic compounds. The influence of the method of obtaining a pigment in the liquid and solid phases on its physicochemical properties and intensity has been studied. The gross formula of the pigment is given and the areas of its practical application are shown. Thermal analysis on a Setaram LabSys Evo instrument (France) was used to study the thermal stability of a highly intense pigment of the organic copper phthalocyanine pigment, which was compared with the closest analog, the copper phthalocyanine pigment. The results of the mass loss of the pigment upon heating are presented. It is shown that, due to the content of phosphorus-containing compounds, the synthesized pigment has high heat resistance and intensity. Thermal studies of exothermic and endothermic processes were carried out in the temperature range of 100-500 °C.